The Influence of Modern Retail-Suppliers Relationships on Suppliers Performance - Dedie Martadisastra; Aekram Faisal (Indonesian Management and Accounting Research, 2020)
The aim of the study was to study the factors of harmonization of behavior of modern retail-suppliers relationships in the supply chain of modern retail suppliers and their impact on suppliers performance. On the other side of the extent to the factors of harmonization behavior (commitment, conflict, conflict management, cooperation and trust) influence the closeness of the modern retail-suppliers relationships. The paper presents the results of a survey of packaged processed foods suppliers which formed part of the wider study of the factors of harmonization behavior. The findings of this study indicate that the results demonstrate the factors of harmonization behavior have varied effects on the closeness of the modern retail-supplier relationships and its impact on suppliers performance and the trust is the most influential factor in modern retail-suppliers relationships. The influence of the modern retail-supplier relationships on suppliers performance is a very strong and significant. The more closely related relationship between modern retail-suppliers is the increasing performance of suppliers. The higher level of interdependence in the relationship or collaboration of the modern retail-suppliers will get a better performance. The influence of factors on the modern retail-suppliers relationships in reality are very complex, not only involves factors of commitment, conflict, conflict management, cooperation and trust, but also involve trading terms, supervising, zoning, store opening hours, distance between outlets modern retail, sanctions and other variables, which are interesting for further research. The results of this study contribute new facts, data and concepts related to the influence model of modern retail-supplier relationship behavior factors, such as commitment, conflict, conflict management, cooperation, and trust, each of which has highly variable effects on supplier performance both financially and non-financially. Further research is needed to refine the results of this initial study.